(untitled) (Third Sector Social Economic Review, 2020)
It has been demonstrated through various studies that individuals with high self-confidence are more successful in their work. Therefore, people must have a certain level of self-confidence in order to succeed in their duties or goals they want to achieve. In professional groups whose target audience is people, this situation makes itself more clear. In this vein, the self-confidence of those who perform teaching profession, which aims to raise ""human beings"", will influence training of creative, solution oriented and self-efficient individuals. In this study, self-confidence of social studies teachers working in secondary schools for teaching has been examined in terms of various variables. Descriptive survey design, one of the quantitative research methods, has been used. The study group of the research consists of 214 social studies teachers working in Sivas province. ""Social Studies Teachers’ Self-Confidence Scale for Teaching"" developed by Uysal and Gürol (2018) has been used as a data collection tool in this study. SPSS package program has been used to analyze the data collected in the research. The findings have been analyzed by means of arithmetic mean, standard deviation, Mann-Whitney U test and Kruskal-Wallis test and whether the data is significant has been evaluated at the level of 0.05 significance. As a result of the research, it has been concluded that the social studies teachers who have participated in the research have high levels of self-confidence for teaching. On the other hand, the self-confidence of social studies teachers for teaching shows a significant difference according to the professional seniority year, gender and graduated department; however, it does not show a significant difference according to the graduated faculty, the school type and weekly course load variables.